Outbreak of Secretary Diarrhea in Kindergarten - Bogadelnikov I.V. Bogadelnikov I.V; Prokudina L.I. Prokudina L.I; Usova S.V. Usova S.V; Dyabina T.A. Dyabina T.A; Romanenko S.P. Romanenko S.P (Zaslavsky O.Yu., 2012)
The epidemiological and clinical peculiarities of rotaviral diarrheas in preschool children, observed in the same group of kindergarten are presented in this article.